Predicting Undergraduate Student Retention in STEM Majors Based on Career Development Factors. Issue 1 (March 2017) - Belser, Christopher T.; Prescod, Diandra J.; Daire, Andrew P.; Dagley, Melissa A.; Young, Cynthia Y.
Abstract : A research gap exists with regard to examining the influence of career interventions and career readiness assessments on student retention in college majors related to science, technology, engineering, and mathematics (STEM). To address this gap, the authors examined 3 variables as potential predictors of retention in STEM‐related majors: (a) a STEM‐focused career planning intervention, (b) students' initial major declarations, and (c) changes in scores on a measure of career readiness. Results revealed that all 3 independent variables were significant predictors of STEM retention but did not accurately predict students who would not be retained. These results have implications for undergraduate STEM initiatives, college counselors and career advisors, and researchers investigating the predictors of STEM retention. Future research should include additional predictor variables.